Do antibody–drug conjugates increase the risk of sepsis in cancer patients? A pharmacovigilance study - Xia, Shuang; Zhao, Yi-Chang; Guo, Lin; Gong, Hui; Wang, Yi-Kun; Ma, Rui; Zhang, Bi-Kui; Sheng, Yue; Sarangdhar, Mayur; Noguchi, Yoshihiro; Yan, Miao (Frontiers in Pharmacology, 2022)
Introduction: Antibody-Drug Conjugates (ADCs) produce unparalleled efficacy in refractory neoplasms but can also lead to serious toxicities. Although ADCs-related sepsis has been reported, the clinical features are not well characterized in real-world studies. Objective: The aim of this study is to identify the association between ADCs and sepsis using FAERS data and uncover the clinical characteristics of ADCs-related sepsis. Methods: We performed disproportionality analysis using FAERS data and compared rates of sepsis in cancer patients receiving ADCs vs other regimens. Associations between ADCs and sepsis were assessed using reporting odds ratios (ROR) and information component (IC). For each treatment group, we detected drug interaction signals, conducted subgroup analyses (age, gender, regimens), and sensitivity analyses. Results: 24,618 cases were reported with ADCs between Q1,2004 to Q3,2021. Sepsis, septic shock, multiple organ dysfunction syndrome and other sepsis-related toxicities were significantly associated with ADCs than other drugs in this database. Sepsis and multiple organ dysfunction syndrome have the highest safety concerns with ADCs compared with other anticancer monotherapies. Gemtuzumab ozogamicin and inotuzumab ozogamicin showed elevated safety risks than other ADCs. For the top 9 ADCs-related sepsis, males showed higher sepsis safety concern than females (p<0.001), however, age did not exert influence on the risk of sepsis. 973 of 2441 (39.9%) cases were acute myeloid leukaemia (AML). 766 of 2613 (29.3%) on ADCc died during therapy. Time-to-onset analysis indicated ADCs-related sepsis is prone to occur within a month after administration. Co-administration of ADCs with colony stimulating factors, proton pump inhibitors, H2-receptor antagonists, or CYP3A4/5 inhibitors showed to synergistically increase the risk of sepsis-related toxicities. Conclusion: Antibody-Drug Conjugates may increase the risk of sepsis in cancer patients, leading to high mortality. Further studies are warranted to characterize the underlying mechanisms and design preventive measures for ADCs-related sepsis.